The Effect of STEM-Based Interventions on Learning Outcomes in High School: A Meta-Analysis - Fadillah, Muhammad Aizri; Hirahmah, Atifah; Asrizal; Usmeldi (Journal of Innovative Physics Teaching, 2024)
While numerous studies have investigated the effectiveness of STEM (Science, Technology, Engineering, and Mathematics) education, findings remain fragmented, and variations in research designs, sample characteristics, and contexts of implementation pose challenges in drawing generalized conclusions. This study aimed to assess the efficacy of the STEM approach on student learning outcomes at the high school level through a meta-analysis. A total of 24 studies that met the inclusion criteria were analyzed from 14 papers that met the criteria. The meta-analysis results demonstrated that the STEM approach was significantly more effective than traditional learning methods, with an overall effect size value of d = 1.71, Z = 7.45, and a significance level of P < 0.00001. Although there was considerable heterogeneity among the effect sizes (Q = 589.66, I² = 96%), the funnel plot demonstrated a symmetrical distribution of effect sizes, indicating minimal publication bias. The findings substantiate that STEM-based education can enhance student engagement, facilitate concept comprehension, and cultivate critical thinking abilities. The practical implications of this study include recommendations for education policymakers to design more effective STEM programs and for educators to adopt STEM-based teaching strategies. Various stakeholders must collaborate to guarantee this initiative's successful implementation and adequately prepare students for the global challenges they will encounter in the 21st century.